Keuntungan Pendidikan Islam Bagi Karakter Generasi Muda - Ika Ika; Ria Noviani (STIKes Ibnu Sina Ajibarang, 2024)
This article discusses the important of Islamic education in building the character of the younger generation. Nowadays,many young people are entangled in things that are not in accordance with good character. The goal is to teach universal values that can be embraced by all level of society. Thus,Islamic education not only plays an important role in shaping the character of the younger generation,but also contributes to the development of society and the nation. This research uses qualitative method,to obtain data through literature study,about the process of character building for the younger generation. Islamic education can help the younger generation to understand moral and spiritual values that are very important for human life.